Impact of drug susceptibility on treatment outcome in sputum smear positive pulmonary tuberculosis patients receiving category-II regimen in RNTCP under field conditions in an urban setting - P. M., Ramesh; M., Saravanan (International Journal of Advances in Medicine, 2018)
Background: The study was conducted with the aim to evaluate the pre-treatment drug susceptibility profile and to assess the influence of drug resistance on treatment outcome among patients treated with category- II (cat- II) regimen under programme conditions. Methods: This study was conducted on 58 smear positive patients with history of previous anti-tuberculosis treatment for more than one month, comprising cases of ‘Failure’, ‘Treatment after Default’ (TAD) and ‘Relapse’. They received cat- II regimen in Chennai Corporation, RNTCP (revised National tuberculosis control programme) centers from July 2006 to September 2006 and they were monitored upto July 2007 as per RNTCP guidelines to assess the outcome of cat-II treatment by sputum smear status. Results: Male dominance (n=40) was seen in the study participants. Most common age group affected was 35-44 years (n=20). Out of 57 cases, 50.9% cases come under ‘Relapse’, 26.3% arises from ‘TAD’ and 22.8% cases were from ‘Failure’. After completion of treatment with cat-II regimen, out of 57 patients 33 patients were cured and 11 cases were into the category of failure, 10 patients were defaulted during treatment and 3 were died. Conclusions: Besides, the low treatment efficiency in MDR-TB cases, cat- II regimen was effective in sensitive and INH resistant cases.